In vivo importance of homologous recombination DNA repair for mouse neural stem and progenitor cells. - Laure Rousseau (Public Library of Science (PLoS), 2012)
We characterized the in vivo importance of the homologous recombination factor RAD54 for the developing mouse brain cortex in normal conditions or after ionizing radiation exposure. Contrary to numerous homologous recombination genes, Rad54 disruption did not impact the cortical development without exogenous stress, but it dramatically enhanced the radiation sensitivity of neural stem and progenitor cells. This resulted in the death of all cells irradiated during S or G2, whereas the viability of cells irradiated in G1 or G0 was not affected by Rad54 disruption. Apoptosis occurred after long arrests at intra-S and G2/M checkpoints. This concerned every type of neural stem and progenitor cells, showing that the importance of Rad54 for radiation response was linked to the cell cycle phase at the time of irradiation and not to the differentiation state. In the developing brain, RAD54-dependent homologous recombination appeared absolutely required for the repair of damages induced by ionizing radiation during S and G2 phases, but not for the repair of endogenous damages in normal conditions. Altogether our data support the existence of RAD54-dependent and -independent homologous recombination pathways.